Developing Microlearning-Based English Video Materials For Junior High School - I Kadek Wira Dana; Putu Kerti Nitiasih; Made Hery Santosa (Institut Agama Islam Negeri Palopo, 2023)
This study proposed developing micro-learning-based English video materials for junior high school. This study was designed in the form of successive approximation model (SAM) by Allen (2012) to design some phases namely preparation phase, iterative phase, and iterative development phase. The English video materials needed were identified based on the observation, interview the English teacher, and interview the learners. The study found that the lesson plans did not provide learning video materials and the lesson plans did not provide suitable teaching model in learning English. Furthermore, the English teachers used conventional model in teaching and learning process and did not provide learning media to assist them in the teaching and learning process. Based on the interview with the English teachers, the researcher concluded that the learners were still having difficulties to understand materials and they have short memorization in learning English. It could be seen from the result of interview with the English teachers and the learners.Â Moreover, the English teachers need the suitable learning media to assist the learners in the learning process. Therefore, the researcher developed three English video materials used the micro-learning concept and combined with three teaching model namely; problem-based learning, project-based learning and discovery-based learning. The effectiveness of the develop English video materials for the learners of junior high school was evaluated using criteria of a good English materials suggested by the formula proposed by Nurkancana and Sunartana (2011). The result showed that the quality of developing micro-learning-based English video materials for junior high school was good. Thus, the micro-learning based English video materials were good to be used as a teaching and learning English video materials for eight grade junior high school students in Denpasar.